Mapping the Knowledge of Antipsychotics-Induced Sudden Cardiac Death: A Scientometric Analysis in CiteSpace and VOSviewer - Wang, Min; Ma, Yixun; Shen, Zefang; Jiang, Lufang; Zhang, Xiaoyuan; Wei, Xuan; Han, Zhengqi; Liu, Hongxia; Yang, Tiantong (Frontiers in Psychiatry, 2022)
The drugs on the market for schizophrenia are first-generation and second-generation antipsychotics. Some of the first-generation drugs have more side effects than the other drugs, so they are gradually no longer being applied clinically. Years of research have shown that the risk of sudden cardiac death in psychotic patients is associated with drug use, and antipsychotic drugs have certain cardiotoxicity and can induce arrhythmias. The mechanism of antipsychotic-induced sudden cardiac death is complicated. Highly cited papers are among the most commonly used indicators for measuring scientific excellence. This article presents a high-level analysis of highly cited papers using Web of Science core collection databases, scientometrics methods, and thematic clusters. Temporal dynamics of focus topics are identified using a collaborative network (author, institution, thematic clusters, and temporal dynamics of focus topics are identified), keyword co-occurrence analysis, co-citation clustering, and keyword evolution. The primary purpose of this study is to discuss the visual results, summarize the research progress, and predict the future research trends by bibliometric methods of CiteSpace and VOSviewer. We discuss relevant key articles briefly and also provide ideas for future research directions for more researchers to conduct related research.